Groundwater Level Fluctuation in Response to Climatic Variation and its Geotechnical Implication in Part of Awgu Shale, Central Benue Trough, Nigeria - ., Umar; Degree, Nuhu; ., Idris; Giza, Ibrahim; Aliyu Itari, Abdullahi (International Journal of Advanced Geosciences, 2018)
The role of climate variation on groundwater level and its geotechnical implication was studied. Static water levels (SWL) and elevations of 57 dug wells and boreholes were measured during dry and wet seasons. The differences between the SWL for dry and wet season was used to establish the depth of groundwater fluctuation, while geophysical investigation was conducted to delineate the subsurface geo-electric layers. This information is vital for groundwater assessment and evaluation, however, this research is biased towards its geotechnical implications. SWL varied between 5.5 â€“ 13 and 2.2 - 9.2 meters below sea level (mbsl), while groundwater elevation ranges from 131.8 â€“ 157.2 and 136-160 meters above sea level (masl) for dry and wet seasons respectively. The depth of fluctuation (active zone) lies between 1.1 â€“ 5.9 mbsl. The wells showed a direct rapid response to short term seasonal precipitation attributable to climate variation, which implies a shallow aquifer. Groundwater flows from the northern parts towards the southern parts. Foundations in the study area are underlain by sandy-clays, clays and sands as revealed by geophysical investigations. Engineering structures with shallow foundation may be prone to shrink-swell behavior, and should be laid beyond active zone.Â Â